FIQIH LEARNING AND SOCIAL-ENTREPRENEURIAL COMPETENCE OF STUDENTS IN ISLAMIC BOARDING SCHOOL - Zulfiyatul Hosnah; Nashrullah; Mufidatul Hasanah; Afifah Nur Aisyah; Della Putri Qurrota A'yun (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2026)
This study examines the effect of fiqh learning on students’ socio-entrepreneurial competence at An-Nashiriyah Islamic Boarding School, Bawean, Gresik. The issue is significant because fiqh learning in pesantren is often perceived as being dominated by ritual worship, whereas muamalah fiqh contains pedagogical resources for developing social ethics, independence, and Islamic value-based entrepreneurship. This research employed a quantitative explanatory design. The population consisted of 98 female students, while 35 students were selected purposively because they actively participated in muamalah fiqh learning and pesantren-based economic activities. Data were collected through questionnaires, observation, and documentation, and then analyzed using descriptive statistics and simple linear regression. The results show that the mean score of fiqh learning was 34.23 with a standard deviation of 3.881, while the mean score of socio-entrepreneurial competence was 51.40 with a standard deviation of 6.367. The regression analysis produced a coefficient of 1.312 with a significance level of <0.001 and an R Square of 0.639. These findings indicate that fiqh learning has a positive and significant effect on students’ socio-entrepreneurial competence and explains 63.9% of its variance. The article argues that contextual and applicable muamalah fiqh learning can serve as a strategic instrument for integrating social character formation, Islamic business ethics, and students’ independence within an island-based pesantren ecosystem. Thus, the results of this study make an important contribution to the development of the pesantren curriculum, especially in designing fiqh muamalah learning that is more contextual, participatory, and oriented towards strengthening the social-entrepreneurial competence of students as a provision for life in the community.